Exploration de la résolution de problèmes à la maternelle à l’aide d’une approche interdisciplinaire en sciences et en arts - Allard, Edith; Samson, Ghislain (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
Our qualitative study explores the ways in which six children of kindergarten age made use of their problem solving skills during interdisciplinary activities combining science and arts. Data were collected through participant observation over the course of four activities and were interpreted using contextual analysis. Results show that children resorted to their problem solving skills as much during scientific activities as during artistic ones, and did so through various strategies. Therefore, we recommend the use of this approach for kindergarten teachers. We further acknowledge the small sample size and short duration of the research and recommend additional studies be conducted. Key words: problem solving, interdisciplinary approach, science, arts, pre-school education, kindergarten